2006
DOI: 10.1136/aim.24.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Are Minimal, Superficial Or Sham Acupuncture Procedures Acceptable as Inert Placebo Controls?

Abstract: Most controlled trials of acupuncture have used minimal, superficial, sham, or ‘placebo’ acupuncture. It has recently been demonstrated that light touch of the skin stimulates mechanoreceptors coupled to slow conducting unmyelinated (C) afferents resulting in activity in the insular region, but not in the somatosensory cortex. Activity in these C tactile afferents has been suggested to induce a ‘limbic touch’ response resulting in emotional and hormonal reactions. It is likely that, in many acupuncture studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
201
1
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(216 citation statements)
references
References 22 publications
1
201
1
13
Order By: Relevance
“…67 Currently, some papers have suggested that sham acupuncture may not be inert. 68,69 Superficial needling was found to be superior to the placebo diazepam. 70 It will be necessary to re-examine trials of acupuncture in which the sham was assumed to be inert, but was not inert.…”
Section: Discussionmentioning
confidence: 99%
“…67 Currently, some papers have suggested that sham acupuncture may not be inert. 68,69 Superficial needling was found to be superior to the placebo diazepam. 70 It will be necessary to re-examine trials of acupuncture in which the sham was assumed to be inert, but was not inert.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among non-pharmaceutical trials, we found that indistinguishability was more frequent for trials of acupuncture but all these indistinguishable placebos consisted of potentially genuine treatments. In acupuncture trials, the use of invasive sham acupuncture techniques has been criticised because the mechanism behind the effects of acupuncture may not depend on the depth or location of needling, but on needling itself [98,144]. Accordingly, the lack of a clear understanding on the mechanisms underlying specific therapeutic effects is also a challenge to the design of indistinguishable placebos in other complex interventions [66].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even a light touch can illicit changes in the limbic system, making it difficult to design a true control for physical modalities. 73 Despite controversy over a lack of adequate blinding and potential intellectual biases against acupuncture and other complementary therapies, evidence exists to support these therapies even at the mechanistic level. 14,[74][75][76] For example, several animal models have shown a therapeutic effect for acupuncture and other CAM therapies.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Furthermore, since animals likely do not understand the difference between true vs sham therapies, we can infer that they are not likely to exhibit a placebo response. [71][72][73][74][75][76][77][78][79][80][81] Some argue that acupuncture is no better than placebo since a few human studies showed no significant difference between sham needling and true acupuncture-ignoring the effects of needle insertion itself. 82 Nevertheless, blinding attempts with non-penetrating shams are possible in humans.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%